Nicotine delivery, retention and pharmacokinetics from various electronic cigarettes. (11th November 2015) - St.Helen, Gideon; Havel, Christopher; Dempsey, Delia A.; Jacob, Peyton; Benowitz, Neal L.
Abstract: Aims: To measure the systemic retention of nicotine, propylene glycol (PG) and vegetable glycerin (VG) in electronic cigarette (e‐cigarette) users, and assess the abuse liability of e‐cigarettes by characterizing nicotine pharmacokinetics. Design: E‐cigarette users recruited over the internet participated in a 1‐day research ward study. Subjects took 15 puffs from their usual brand of e‐cigarette. Exhaled breath was trapped in gas‐washing bottles and blood was sampled before and several times after use. Setting: San Francisco, California, USA. Participants: Thirteen healthy, experienced adult e‐cigarette users (six females and seven males). Measurements: Plasma nicotine was analyzed by gas chromatography–mass spectrometry (GC‐MS/MS) and nicotine, VG and PG in e‐liquids and gas traps were analyzed by LC‐MS/MS. Heart rate changes and subjective effects were assessed. Findings: E‐cigarettes delivered an average of 1.33 (0.87‐1.79) mg [mean and 95% confidence interval (CI)] of nicotine, and 93.8% of the inhaled dose, 1.22 (0.80‐1.66) was systemically retained. Average maximum plasma nicotine concentration (Cmax ) was 8.4 (5.4–11.5) ng/ml and time of maximal concentration (Tmax ) was 2–5 minutes. One participant had Tmax of 30 minutes. 84.4% and 91.7% of VG and PG, respectively, was systemically retained. Heart rate increased by an average of 8.0 beats per minute after 5 minutes. Withdrawal and urge to smoke decreased and the e‐cigarettes were described as satisfying. Conclusions: E‐cigarettes can deliver levels of nicotine that are comparable to or higher than typical tobacco cigarettes, with similar systemic retention. Although the average maximum plasma nicotine concentration in experienced e‐cigarette users appears to be generally lower than what has been reported from tobacco cigarette use, the shape of the pharmacokinetic curve is similar, suggesting addictive potential.